Cover Picture: Energy Savings in the Conversion of CO2 to Fuels using an Electrolytic Device (Energy Technol. 6/2014). Issue 6 (June 2014) - Bevilacqua, Manuela; Filippi, Jonathan; Lavacchi, Alessandro; Marchionni, Andrea; Miller, Hamish A.; Oberhauser, Werner; Vesselli, Erik; Vizza, Francesco
<x xml:space="preserve">Abstract</x> CO2 Valuation to Fuels and Chemicals: A key challenge for the valorization of carbon dioxide to fuels and chemicals is represented by the design and the realization of practical electrolyzers, capable of converting CO2 to useful products with a reduced energy consumption and high material stability. The cover image highlights the different working conditions of a traditional—"water‐based"—CO2 electrolyzer and the novel depolarized‐anode alkaline membrane CO2 electrolyzer (DAAM–CE). The Communication delivered by Manuela Bevilacqua and Francesco Vizza of the Institute of Organometallic Chemistry of the Italian National Research Council (ICCOM‐CNR, Florence) and coworkers is presented on page 522 and it demonstrates the great potential of the DAAM–CE device. The key point of this device is the exploitation of the anodic alcohol oxidation instead of water electrolysis to oxygen; in other words, the DAAM–CE device combines the cathodic transformation of CO2 into useful fuels (CH4, C2H4, and HCOO−) with the anodic oxidation of ethanol to acetate. At the same time, the presence of ethanol guarantees a working cell potential much lower than existing architectures, leading to a net reduction in energy consumption from 130 kWh to 77 kWh (per kg of hydrocarbon products) with respect to a traditional device. It is noteworthy that the materials in these devices (e.g., membranes and electrocatalysts) show long‐term stability under these conditions.<boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>